POTENTIALS FOR THE WINE TOURISM EXPANSION IN THE MUNICIPALITY OF ALEKSANDROVAC IN THE FUNCTION OF SUSTAINABLE DEVELOPMENT - Petrović, Dragan; Vukoičić, Danijela; Milinčić, Uroš; Milinčić, Miroljub (Economic Outlook, 2022)
This paper presents the wine heritage of the municipality of Aleksandrovac, highlights the potential of wine tourism in this area and analyzes the factors that motivate and attract this selective form of tourism. The primary goal of the paper is to determine the possibility and perspectives of wine tourism development, but also the sustainable development of the municipality of Aleksandrovac, its surroundings and this part of Serbia through research, analysis and comparison. The task of the paper is to systematize the existing knowledge and define the segments of the wine tourism offer in the function of sustainable development.
Keywords: wine tourism; sustainable development; Aleksandrovac; Serbia